Hypomyelinating Leukodystrophy with Spinal Cord Involvement Caused by a Novel Variant in RARS: Report of Two Unrelated Patients - Rezaei, Zahra; Hosseinpour, Sareh; Ashrafi, Mahmoud Reza; Mahdieh, Nejat; Alizadeh, Houman; Mohammadpour, Masoud; Khosroshahi, Nahideh; Amanat, Man; Tavasoli, Ali Reza (Neuropediatrics, 2019)
Leukodystrophies are heterogeneous group of genetic white matter disorders with a wide range of neurologic and systemic manifestations. Defects in genes encoding aminoacyl tRNA (transfer ribonucleic acid) synthetase enzymes (aaRSs) are recently identified as the etiology of some leukodystrophies. Herein, we described two unrelated children referred to Children's Medical Center, Tehran, Iran, with developmental delay, nystagmus, seizures, psuedo-bulbar palsy and dystonia. Whole exome sequencing (WES) in both patients identified a homozygous (c.2T > C) variant in exon one of RARS gene, encoding cytoplasmic arginyl-tRNA synthetase. Our finding was confirmed by segregation analysis. In silico analyses of the c.2T > C variant showed its possible pathogenic role due to the absence of the start codon. Severe hypomyelination was the common neuroimaging finding of both cases. Spinal cord involvement was found in one of our patients which was not previously reported in studies. We, therefore, showed that RARS-related hypomyelination might affect spinal cord.
Keywords: leukodystrophy; hypomyelination; children; RARS gene